A Preliminary Single-Cell RNA-Seq Analysis of Embryonic Cells That Express Brachyury in the Amphioxus, Branchiostoma japonicum - Satoh, Noriyuki; Tominaga, Hitoshi; Kiyomoto, Masato; Hisata, Kanako; Inoue, Jun; Nishitsuji, Koki (Frontiers in Cell and Developmental Biology, 2021)
Among chordate taxa, the cephalochordates diverged earlier than urochordates and vertebrates; thus, they retain unique, primitive developmental features. In particular, the amphioxus notochord has muscle-like properties, a feature not seen in urochordates or vertebrates. Amphioxus contains two Brachyury genes, Bra1 and Bra2. Bra2 is reportedly expressed in the blastopore, notochord, somites, and tail bud, in contrast to a low level of Bra1 expression only in notochord. To distinguish the expression profiles of the two Brachyury genes at the single-cell level, we carried out single-cell RNA-seq (scRNA-seq) analysis using the amphioxus, Branchiostoma japonicum. This scRNA-seq analysis classified B. japonicum embryonic cells into 15 clusters at developmental stages from midgastrula to early swimming larva. Brachyury was expressed in cells of clusters 4, 5, 8, and 9. We first confirmed that cluster 8 comprises cells that form somites since this cluster specifically expresses four myogenic factor genes. Cluster 9 contains a larger number of cells with high levels of Bra2 expression and a smaller number of cells with Bra1 expression. Simultaneous expression in cluster 9 of tool-kit genes, including FoxA, Goosecoid, and hedgehog, showed that this cluster comprises cells that form the notochord. Expression of Bra2, but not Bra1, in cells of clusters 4 and 5 at the gastrula stage together with expression of Wnt1 and Caudal indicates that clusters 4 and 5 comprise cells of the blastopore, which contiguously form the tail bud. In addition, Hox1, Hox3, and Hox4 were highly expressed in Bra2-expressing clusters 4, 5, 8, and 9 in a temporally coordinated manner, suggesting roles of anterior Hox genes in specification of mesodermal organs, including somites, notochord, and tail bud. This scRNA-seq analysis therefore highlights differences between the two Brachyury genes in relation to embryonic regions in which they are expressed and their levels of expression. Bra2 is the ancestral Brachyury in amphioxus, since expression in the blastopore is shared with other deuterostomes. On the other hand, Bra1 is a duplicate copy and likely evolved a supplementary function in notochord and somite formation in the Branchiostoma lineage.